Clinical Profile and Prognostic Factors of Mortality in Elderly Covid-19 at Ansari Saleh Hospital - Agung SNC, Wiwit; Erianty, Erni; Khairina, Ana (Fakultas Kedokteran Universitas Brawijaya, 2024)
Morbidity and mortality of elderly with Covid-19 are higher than in adults. This study aimed to determine the prognostic factors of mortality in elderly with Covid -19. This research was a retrospective cohort study in patients aged 60 years and older with a PCR-confirmed diagnosis of Covid -19 admitted to Ansari Saleh Hospital, South Kalimantan, Indonesia between January to July 2021. Data on age, sex, comorbidities, symptoms, physical examinations, laboratory examinations, chest x-rays, and Covid severity degree were collected, univariate and multivariate analyses performed to determine the independent prognostic factors. The research results showed 209 samples met the criteria. The average age was 66,94 years, dominated by men (57.9%). The most common comorbidities were hypertension (48.8%), diabetes mellitus (35.4%), and chronic heart failure (8.1%). The most frequent symptoms were dyspnea (79.9%), cough (74.2%), and fever (56.5%). Patients treated mostly had severe/critical degree of Covid -19 (140 patients, or 67%). The results of multivariate logistic regression analysis on the variables of respiratory rate (p=0.009; OR=1.1), NLR level (p=0.002; OR=1.081), age (p=0.025; OR=2.479) and Covid severity degree (p=0.008; OR=8.206) showed significant results as independent prognostic factors of mortality. Covid severity degree variable has the highest prognostic level; patients with severe Covid degree have an 8.206 times higher chance of death than mild-to-moderate degrees. In conclusion, respiratory rate, NLR level, age, and Covid severity degree can act as prognostic factors of mortality in elderly suffering from Covid-19.